Inhibition of Aldose Reductase Prevents Experimental Allergic Airway Inflammation in Mice - Yadav, Umesh C. S.; Ramana, Kota V.; Aguilera-Aguirre, Leopoldo; Boldogh, Istvan; Boulares, Hamid A.; Srivastava, Satish K. (PloS one, 2009)
The bronchial asthma, a clinical complication of persistent inflammation of the airway and subsequent airway hyper-responsiveness, is a leading cause of morbidity and mortality in critically ill patients. Several studies have shown that oxidative stress plays a key role in initiation as well as amplification of inflammation in airways. However, still there are no good anti-oxidant strategies available for therapeutic intervention in asthma pathogenesis. Most recent studies suggest that polyol pathway enzyme, aldose reductase (AR), contributes to the pathogenesis of oxidative stress-induced inflammation by affecting the NF-kappaB-dependent expression of cytokines and chemokines and therefore inhibitors of AR could be anti-inflammatory. Since inhibitors of AR have already gone through phase-III clinical studies for diabetic complications and found to be safe, our hypothesis is that AR inhibitors could be novel therapeutic drugs for the prevention and treatment of asthma. Hence, we investigated the efficacy of AR inhibition in the prevention of allergic responses to a common natural airborne allergen, ragweed pollen that leads to airway inflammation and hyper-responsiveness in a murine model of asthma. Primary Human Small Airway Epithelial Cells (SAEC) were used to investigate the in vitro effects of AR inhibition on ragweed pollen extract (RWE)-induced cytotoxic and inflammatory signals. Our results indicate that inhibition of AR prevents RWE -induced apoptotic cell death as measured by annexin-v staining, increase in the activation of NF-kappaB and expression of inflammatory markers such as inducible nitric oxide synthase (iNOS), cycloxygenase (COX)-2, Prostaglandin (PG) E(2), IL-6 and IL-8. Further, BALB/c mice were sensitized with endotoxin-free RWE in the absence and presence of AR inhibitor and followed by evaluation of perivascular and peribronchial inflammation, mucin production, eosinophils infiltration and airway hyperresponsiveness. Our results indicate that inhibition of AR prevents airway inflammation and production of inflammatory cytokines, accumulation of eosinophils in airways and sub-epithelial regions, mucin production in the bronchoalveolar lavage fluid and airway hyperresponsiveness in mice. These results suggest that airway inflammation due to allergic response to RWE, which subsequently activates oxidative stress-induced expression of inflammatory cytokines via NF-kappaB-dependent mechanism, could be prevented by AR inhibitors. Therefore, inhibition of AR could have clinical implications, especially for the treatment of airway inflammation, a major cause of asthma pathogenesis.